Power contestation and regulation in digital platform ecosystems - The case of the EU's Digital Markets Act - Victorine Verlooy; Vincent Heimburg; Maximilian Schreieck; Manuel Wiesche (Electronic Markets, 2026)
In this study, we investigate how power contestation between complementors and powerful platform owners unfolds in digital platform ecosystems as they come under regulatory scrutiny. Platform owners like Alphabet/Google, Apple, Amazon, and Meta/Facebook dominate their respective ecosystems, leveraging network effects and market power to maintain their positions, giving them a powerful advantage vis-à-vis supply-side complementors. Complementors have become increasingly dependent on these platforms and struggle due to their weakened position. In the EU, the European Commission has implemented the Digital Markets Act, which aims to increase fairness and contestability within and across digital platform ecosystems. Using a case study approach, we analyze how regulatory scrutiny, such as the Digital Markets Act, has affected power contestation between platform owners and complementors. In particular, we investigate app store and search platform ecosystems. We establish a conceptual framework of power contestation that shows how complementors and platform owners interact directly and through the regulator as a mediator, vying for power in the ecosystem. We thereby contribute to the emerging Information Systems literature on power dynamics and the regulation of digital platform ecosystems.
Keywords: L50; M15; 620; Digital platform ecosystems; Platform power; Platform owners; Complementors; Digital Markets Act (DMA); Regulation